Management of Labour Migration and Its Impact on Rural Sustainable Development: The Case of Ukraine - Svitlana LUKASH; Olena PIZNIAK; Alina BRYCHKO; Nataliia MASLAK; Oleksandr MASLAK (Communications of International Proceedings, 2020)
Labor migration is the main type of world migration in the XXI century. The paper summarizes the key routes through which internal and international migration impact rural development and some of the evidence pertaining to these effects in low-income countries. It concludes that, although the study of migration impacts on rural economies has come a long way from the early dual theories of development, some of the potentially more important aspects remain to be investigated systematically. International labor migration is a complex and ambiguous phenomenon and is a process of territorial interstate movement. Labor migration is a common feature of economic development. The main causes of labor migration in the world are analyzed and Ukraine is singled out. The mobility of people for temporary or permanent employment is a common characteristic of agricultural activity. In some regions, especially in rural areas, there are incredibly significant migration flows, which have a significant impact on people, households, and regions of origin. Despite the growing debate about the motivations and consequences of recent migration flows, the costs and benefits of this global phenomenon remain unclear and remain far beyond public policy. The purpose of this paper is to review key issues related to labor migration in rural areas; analysis of the impact of migration processes on economic development; identification of the main directions of migration management for improvement in interconnection of state governance and business representatives.
Keywords: migration; international labour migration; labour market; rural development; business; sustainable development